(untitled) (Journal of Economic Research & Business Administration, 2016)
In article experience of stimulation of small and medium business in industrially developed countries, the developing states and in transitional economies is considered. The events for business support held in the USA, Canada, Australia, New Zealand, Germany, Japan, India, Singapore, China, Denmark, the Netherlands, France, Belgium, Spain and other countries are analysed. The special attention is paid to the analysis of foreign practice of stimulation of small and average business and studying of possibility of adaptation of foreign experience to Kazakhstan. As a result of the review of foreign experience the elements of financial, innovative, institutional support of subjects of business, most important for Kazakhstan, were defined. The analysis of experience of the countries of the Central and Eastern Europe also allowed to reveal a number of ways of the state assistance to creation of new workplaces, actual for Kazakhstan.